Comparison of the perioperative complications of high intensity focused ultrasound vs. laparoscopic surgery for uterine fibroids: a retrospective study - Hu, Li; Fang, Chunling; Tang, Nenghuan; Xu, Fan (Frontiers in Surgery, 2025)
ObjectiveTo compare the perioperative complications following high intensity focused ultrasound (HIFU) or laparoscopic surgery for uterine fibroids.MethodsA retrospective cohort was conducted involving patients with uterine fibroids (UFs) who underwent HIFU or laparoscopic surgery. The primary outcome was the incidence of perioperative complications. Secondary outcomes included the Numerical Rating Scale (NRS) for pain assessment, duration of hospital stay, hospitalization costs, and the incidence of short-term postoperative complications within 1 month. Univariate and multivariate logistic regression analyses were conducted to identify the influencing factors.ResultsA total of 140 patients were included in the study, with an overall perioperative complication rate of 72.9%. Among them, 46 patients underwent HIFU treatment, while 94 underwent laparoscopic surgery. The HIFU group experienced significantly fewer total complications (52.2% vs. 83.0%, P < 0.001) and grade ≥ II complications (4.3% vs. 26.6%, P = 0.021) compared to the laparoscopic group. Further multivariate logistic regression revealed that treatment modality (Laparoscopic Surgery vs. HIFU: OR 5.48, 95% CI: 1.17–25.65, P = 0.031) was independent risk factors for grade ≥ II complications. Moreover, the HIFU group also experienced less pain on postoperative day 1, 2, and 3 compared to the laparoscopic surgery group (2.50 vs. 4.00, P < 0.001; 1.00 vs. 4.00, P < 0.001; 1.00 vs. 3.00, P < 0.001; respectively). Additionally, subgroup analyses showed that laparoscopic myomectomy (LM) group had fewer grade ≥ II complications than laparoscopic hysterectomy (LH) group (15.4% vs. 40.5%, P = 0.006).ConclusionHIFU treatment is associated with a lower rate of perioperative complications, including grade ≥ II complications, reduced postoperative pain, shorter hospital stays, and lower hospitalization costs compared to laparoscopic surgery. These findings suggest that HIFU may serve as a viable alternative strategy for the management of uterine fibroids.